Evaluation of acoustic telemetry grids for determining aquatic animal movement and survival. Issue 6 (30th March 2018) - Kraus, Richard T.; Holbrook, Christopher M.; Vandergoot, Christopher S.; Stewart, Taylor R.; Faust, Matthew D.; Watkinson, Douglas A.; Charles, Colin; Pegg, Mark; Enders, Eva C.; Krueger, Charles C.
Abstract: Acoustic telemetry studies have frequently prioritized linear configurations of hydrophone receivers, such as perpendicular from shorelines or across rivers, to detect the presence of tagged aquatic animals. This approach introduces unknown bias when receivers are stationed for convenience at geographic bottlenecks (e.g. at the mouth of an embayment or between islands) as opposed to deployments following a statistical sampling design. We evaluated two‐dimensional acoustic receiver arrays (grids: receivers spread uniformly across space) as an alternative approach to provide estimates of survival, movement and habitat use. Performance of variably spaced receiver grids (5–25 km spacing) was evaluated by simulating (1) animal tracks as correlated random walks (speed: 0.1–0.9 m/s; turning angle SD : 5–30°); (2) variable tag transmission intervals along each track (nominal delay: 15–300 s); and (3) probability of detection of each transmission based on logistic detection range curves (mid‐point: 200–1, 500 m). From simulations, we quantified (i) time between successive detections on any receiver (detection time), (ii) time between successive detections on different receivers (transit time), and (iii) distance between successive detections on different receivers (transit distance). In the most restrictive detection range scenario (200 m), the 95th percentile of transit time was 3.2 days at 5 km, 5.7 days at 7 km and 15.2 days at 25 km grid spacing; for the 1, 500 m detection range scenario, it was 0.1 days at 5 km, 0.5 days at 7 km and 10.8 days at 25 km. These values represented upper bounds on the expected maximum time that an animal could go undetected. Comparison of the simulations with pilot studies on three fishes (walleye Sander vitreus, common carp Cyprinus carpio and channel catfish Ictalurus punctatus ) from two independent large lake ecosystems (lakes Erie and Winnipeg) revealed shorter detection and transit times than what simulations predicted. By spreading effort uniformly across space, grids can improve understanding of fish migration over the commonly employed receiver line approach, but at increased time cost for maintaining grids.